2011
DOI: 10.2217/dmt.11.60
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fear of hypoglycemia in children with Type 1 diabetes and their parents

Abstract: SUMMARY This article summarizes the literature on fear of hypoglycemia in pediatric Type 1 diabetes and the assessment of this fear in both children with Type 1 diabetes and their parents. The most common instrument for assessing fear of hypoglycemia in this population is the children’s and parent’s versions of the Hypoglycemia Fear Survey (HFS), although studies using other assessment measures are also reviewed. Studies using this survey have identified variables contributing to fear of hypoglycemia in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
153
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(171 citation statements)
references
References 70 publications
9
153
0
6
Order By: Relevance
“…In contrast to a previous study 5, but consistent with several other studies 4, 6, 7, 8, 9, 10, 11, 12, 13, HbA 1c was not related to parental fear of hypoglycaemia. HbA 1c was assessed by parental report, and therefore may not be reliable.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to a previous study 5, but consistent with several other studies 4, 6, 7, 8, 9, 10, 11, 12, 13, HbA 1c was not related to parental fear of hypoglycaemia. HbA 1c was assessed by parental report, and therefore may not be reliable.…”
Section: Discussionsupporting
confidence: 90%
“…Most of these studies had small sample sizes ( N ≤200) 4, 5, 8, 9, 10, 11, 12 and did not investigate demographic and clinical characteristics simultaneously 4, 6, 7, 8, 9, 10, 11, 12, 13, limiting the exploration of independent effects. In addition, the associations between parent demographic characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Физическая активность также может быть не-предсказуема. Наиболее распространенной причиной гипогликемии у пациентов молодого возраста явля-ется физическая активность, но, к сожалению, некото-рые пациенты и их родители пытаются уменьшить этот риск чрезмерным потреблением углеводов до, во время и после тренировки [20,21].…”
Section: факторы влияющие на качество жизни пациентов с сдunclassified
“…The recent INTERPRET study, the largest and longest multicenter prospective study to date, has confirmed the effectiveness of CGM in pump users; data from 263 patients using SAP therapy under real-life conditions over 12 months revealed significantly lower rates of hospitalization, greater treatment satisfaction, and reduced fear of hypoglycemia compared to CGM nonusers [31]. Other studies have also shown that the use of CGM and related features such as alarms and automatic insulin suspension (i.e., low glucose suspension [LGS]) reduces fear of hypoglycemia, the incidence of severe hypoglycemic events, and time spent in hypoglycemia [32][33][34][35]. More importantly, the use of the LGS feature does not result in rebound hyperglycemia [33].…”
Section: Introductionmentioning
confidence: 99%